The influence of row spacing, thickness of planting in the row, and seed size on the growth, development and yield of Aquila potatoes in the Dohne sourveld area - Graven, E. H.(Earle Holm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1957.